GROWTH RATE IN LACTARIUS LACTARIUS (SCHNEIDER) AT KARWAR - Kartha, K N Rasachandra (Indian Journal of Fisheries, 2011)
The length-frequency data of the big-jawed jumper, Lactarius lactarius (Schneider), collected from the trawl catches of Karwar coast during 1965-66, 1966-67 and 1967-68 season show that the species attains a length of about 90 mm in six months. The landings from grounds more than 30 meters in depth generally contained bigger individuals, while the near-shore catches were dominated by juveniles.